Explaining the Effectiveness of the Contrast Culture Method for Managing Interpersonal Interactions Across Cultures - Hiratsuka, Hiroyoshi; Suzuki, Hanako; Pusina, Alexis (Journal of International Students, 2016)
One of the current challenges in the field of intercultural education comes from the limited availability of training efficacy studies. The present study focused on explaining the effectiveness of the Contrast Culture Method (CCM) as an intercultural education method for managing interpersonal interactions across cultures between graduate international students and their local counterparts in an academic program in Japan. By incorporating a qualitative methodology through the grounded theory, the study explained a context of domestic interpersonal relations across cultures in Japan. The result showed CCM’s effectiveness based on respondents’ reflective accounts, and supported the ideas suggested by the original study. The article concludes with future directions for research and application of CCM.